Adopting a toolkit to manage time, resources, and expectations in the systematic review process: a case report - Q. Eileen Wafford (University Library System, University of Pittsburgh, 2021)
Background: The proliferation of systematic reviews has impacted library operations and activities as librarians support, collaborate, and perform more tasks in the systematic review process. This case report describes a toolkit that librarians with extensive experience in supporting multiple review teams use to manage time, resources, and expectations in the systematic review process. Case Presentation: The toolkit is a compilation of documents that we use to effectively communicate with and help review teams understand and navigate each stage of the systematic review process. Elements included in the toolkit and discussed in this case report are intake forms, communication templates and memoranda, a process flow diagram, library guides on tools for retrieval and data appraisal, and established standards for guidance during the write-up stage. We describe the use of the toolkit for both education and project management, with a focus on its use in helping manage team time, resources, and expectations. Discussion: The systematic review toolkit helps librarians connect systematic review steps and tasks to actionable items. The content facilitates and supports discussion and learning by both librarians and team members. This toolkit helps librarians share important information and resources for each stage of the process.